Assessment of the Appearance and Toxin Production Potential of Invasive Nostocalean Cyanobacteria Using Quantitative Gene Analysis in Nakdong River, Korea - Yong-Jin Kim; Hae-Kyung Park; In-Soo Kim (Toxins, 2022)
Invasive nostocalean cyanobacteria (INC) were first reported in tropical regions and are now globally spreading rapidly due to climate change, appearing in temperate regions. INC require continuous monitoring for water resource management because of their high toxin production potential. However, it is difficult to analyze INC under a microscope because of their morphological similarity to nostocalean cyanobacteria such as the genus Aphanizomenon. This study calculates the gene copy number per cell for each target gene through quantitative gene analysis on the basis of genus-specific primers of genera Cylindrospermopsis, Sphaerospermopsis, and Cuspidothrix, and the toxin primers of anatoxin-a, saxitoxin, and cylindrospermopsin. In addition, quantitative gene analysis was performed at eight sites in the Nakdong River to assess the appearance of INC and their toxin production potential. Genera Cylindrospermopsis and Sphaerospermopsis did not exceed 100 cells mL−1 at the maximum, with a low likelihood of related toxin occurrence. The genus Cuspidothrix showed the highest cell density (1759 cells mL−1) among the INC. Nakdong River has potential for the occurrence of anatoxin-a through biosynthesis by genus Cuspidothrix because the appearance of this genus coincided with that of the anatoxin-a synthesis gene (anaF) and the detection of the toxin by ELISA.